2006
DOI: 10.1002/ana.21018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intraoperative hypothermia on neuropsychological outcomes after intracranial aneurysm surgery

Abstract: This is the largest prospective evaluation of neuropsychological function after subarachnoid hemorrhage to date. Testing was completed in a high fraction of patients, demonstrating the feasibility of such testing in a large trial. However, the frequent inability to complete testing in poor-outcome patients suggests that testing may be best used to refine outcome assessments in good-grade patients. Many patients showed impairment on at least one test, with global impairment present in 17 to 20% of patients (18-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 44 publications
0
46
0
2
Order By: Relevance
“…Different aspects of executive function thus appear to have different rates of impairment. Among studies conducted in the past 10 years, deficits in cognitive flexibility, as measured by the Wisconsin Card Sorting Task, were found in 8% to 44% of patients with aSAH, 12,13,[15][16][17]19 whereas deficits in inhibition, as measured by the Stroop task, were found in 17% to 56% of patients with aSAH. 13,15,16 A study by Manning and colleagues 43 highlights the need to address different aspects of executive function.…”
Section: Executive Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different aspects of executive function thus appear to have different rates of impairment. Among studies conducted in the past 10 years, deficits in cognitive flexibility, as measured by the Wisconsin Card Sorting Task, were found in 8% to 44% of patients with aSAH, 12,13,[15][16][17]19 whereas deficits in inhibition, as measured by the Stroop task, were found in 17% to 56% of patients with aSAH. 13,15,16 A study by Manning and colleagues 43 highlights the need to address different aspects of executive function.…”
Section: Executive Functionmentioning
confidence: 99%
“…Consequently, the prevalence of executive dysfunction in aSAH survivors is very wide with estimates ranging from 3% to 76%. 10,[12][13][14][15][16][17][18][19]37 Interestingly, self-reported deficits in executive function do not appear to correlate with results from objective cognitive tests; Ravnik and colleagues 38 found that patients with aSAH reported attentional deficits most frequently, yet patients performed better on tests of attention than on tests of other cognitive domains. Discordance between self-reported cognitive deficits and results from objective cognitive tests has also been reported in other domains, like memory.…”
Section: Executive Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no published study has examined the effect of intraoperative neuroprotection strategies used during aneurysm surgery on longitudinal postoperative cognitive function. The IHAST study provided information about the impact of mild intraoperative hypothermia on cognitive performance 3 months after surgery, 5 and this investigation reports recovery beyond that time frame. Use of mild intraoperative hypothermia did not have a significant effect on either composite scores or change in composite scores over time up to 15 months postsurgery, nor did it affect the frequency of patients with impaired cognitive function at different time points.…”
Section: Discussionmentioning
confidence: 99%
“…4 IHAST also assessed neurocognitive function 3 months postsurgery with 5 standard neuropsychological tests, which also failed to demonstrate any effect of intraoperative hypothermia. 5 This provided, however, the opportunity to longitudinally evaluate longer-term patterns of neurocognitive behavior in the study population.…”
mentioning
confidence: 99%